The Effect of Welding Parameters Between Titanium Alloy and Stainless Steel with Interlayer of Aluminium Alloy in Resistance Spot Welding - Chuok, Gan Yee (IRC, 2020)
Resistance spot welding is a common fabrication method used in industry today. This manufacturing process always used for industry today because it is low cost, fast, and convenient in the assembly line. To obtain optimum condition during welding, proper setting of welding parameters such as weld current, electrode force, and weld time are needed. The main reason is welding input parameters affect the weld joint quality of specimens and thus give direct impact to mechanical properties of materials in term of tensile strength, microstructure, and microhardness. Moreover, setting improper welding parameters will contribute to weld defects issue such as expulsion at tested specimens.